Optimization of microstructure for HRE-free Nd-Fe-B magnets with improved properties - Yuxin Zhao; Rui Han; Meng Zheng; Xun Duan; Xiaoning Shi; Xianjun Hu; Hongsheng Chen; Dong Zhou; Shengzhi Dong; Wei Li (Journal of Materials Research and Technology)
In this work, we successfully prepared heavy rare earth (HRE)-free Nd-Fe-B sintered magnets with improved coercivity (Hcj) and remanence (Br) by precisely controlling the grain size and optimizing the grain boundaries (GBs). Employing a low-temperature-sintering process, we achieved varying grain sizes in the magnets. Specifically, the samples sintered at 920 °C had an average grain size of 2.35 μm, while the samples exhibiting the best magnetic properties had an average grain size of 2.51 μm. The fine-crystalline HRE-free magnets sintered at the optimal temperature demonstrated a superior coercivity of 16.29 kOe. Grain size refinement was found to be beneficial for enhancing the thermal stability of the magnets. Electron backscatter diffraction and X-ray diffraction analyses revealed that the fine-crystalline magnets displayed an improved crystallographic orientation, which correlates with the enhanced mobility of the magnetic powders. Transmission electron microscopy results indicated that the GBs in fine-crystalline magnets were thicker, with greater uniformity and continuity at triple junction points. We elaborate on the underlying mechanisms for the simultaneous enhancement of Br and Hcj in detail. Furthermore, first-order reversal curve (FORC) analysis confirmed that the fine-crystalline magnets exhibit superior temperature stability, attributed to a reduced local demagnetization field and a more independent demagnetization process.